Partitioning isotherm and kinetic of erythromycin into mixed reverse micelle during forward transfer - Siti Norazimah, Mohamad-Aziz; Zularisam, A. W.; Mimi Sakinah, A. M. (Elsevier B.V., 2019)
The capacity of AOT (sodium bis (2-ethylhexyl) sulfosuccinate) and SB3-12 (3-(N, NDimethyldodecylammonio) propanesulfonate) mixed reverse micelle for erythromycin adsorption was assessed using the Langmuir, Freundlich, and Sips isotherm models. The kinetic of erythromycin transport was also evaluated using the two-film model. The results indicated that the Langmuir isotherm model exhibits the highest precision based on the regression coefficient data, however, this applies only for the condition of 80.0 to 160.0 g/L of AOT concentration. Error analysis revealed that for a condition where AOT concentration was low, the process fits the Freundlich isotherm model, suggesting that at a surfactant concentration around 20.0 g/L, forward transfer of erythromycin shows physisorption criteria. The Langmuir isotherm data for higher AOT concentration (80.0 g/L) denotes the chemisorption characteristics, by which erythromycin transfer was at the highest degree. This also signifies that high AOT concentration is a favourable condition where stable mixed reverse micelle was available and erythromycin adsorption was accelerated. In addition, the kinetic data complements the two-film theory for a flat interface model and shows that dissemination of erythromycin into the interfacial layer of mixed reverse micelles depended on surfactant concentration. Overall, this study confirms previous findings and contributes additional evidence for erythromycin extraction, under the influence of anionic-zwitterionic surfactant combination and shows superiority towards solubilising biomolecules.